Improvement Design of Pharmaceutical Cartoning Machine Cam Curve based on the B-Spline Motion Law - Wang Xinjian; Guo Lieen; Wang Guanming; Bao Shengwei; Zhang Xianxin (Jixie chuandong)
In order to enhance the movement stability of pharmaceutical cartoning machine and reduce noise,the motion law of cam is improved. The B-spline function motion law is used to replace the original sine acceleration motion law. At the same time,a pharmaceutical cartoning machine cam parameterized software is also developed based on the B-spline function motion law. The problem of the existing in cam parameterized software that can not add more constrained motion control condition is solved and the pharmaceutical cartoning machine cam parameterized software is more practical valuable and universal applicability. Through the experimental verification,after improving the motion law of cam,the noise is decreased obviously in the actual operation. And the products packing quality of cartoning machine is improved obviously. It provides reference to improve this kind of similar cylindrical cam mechanism device.